Odor-active constituents in fresh pineapple (Ananas comosus [L.] Merr.) by quantitative and sensory evaluation. - Tokitomo, Yukiko; Steinhaus, Martin; Büttner, Andrea; Schieberle, Peter (Bioscience Biotechnology and Biochemistry, 2005)
By application of aroma extract dilution analysis (AEDA) to an aroma distillate prepared from fresh pineapple using solvent-assisted flavor evaporation (SAFE), 29 odor-active compounds were detected in the flavor dilution (FD) factor range of 2 to 4,096. Quantitative measurements performed by stable isotope dilution assays (SIDA) and a calculation of odor activity values (OAVs) of 12 selected odorants revealed the following compounds as key odorants in fresh pineapple flavor: 4-hydroxy-2,5-dimethyl-3(2H)-furanone (HDF; sweet, pineapple-like, caramel-like), ethyl 2-methylpropanoate (fruity), ethyl 2-methylbutanoate (fruity) followed by methyl 2-methylbutanoate (fruity, apple-like) and 1-(E,Z)-3,5-undecatriene (fresh, pineapple-like). A mixture of these 12 odorants in concentrations equal to those in the fresh pineapple resulted in an odor profile similar to that of the fresh juice. Furthermore, the results of omission tests using the model mixture showed that HDF and ethyl 2-methylbutanoate are character impact odorants in fresh pineapple.<br